Determinants of α-conotoxin BuIA selectivity on the nicotinic acetylcholine receptor β subunit - Shiembob, David L. (2006)
Neuronal nicotinic acetylcholine receptors (nAChRs) are pentamers composed of α and β subunits. Different molecular compositions of these subunits constitute various receptor subtypes that are implicated in the pathophysiology and/ or treatment of several disease states, but are difficult to distinguish among pharmacologically. α-Conotoxins are a group of small, structurally defined peptides that may be used to molecularly dissect the nAChR binding site. Heteromeric nAChRs generally contain either a β2 or β4 subunit in addition to an α subunit at the ligand-binding interface. α-Conotoxin BuIA kinetically distinguishes between β2- and β4-containing nAChRs with long off-times for the latter. Mutational studies were used to assess the influence of residues that line the putative acetylcholine- binding pocket, but differ between β2 and β4 subunits. Residues Thr/Lys59, Val/Ile111 and Phe/Gln119 of the respective β2- and β4 subunits are critical to off-rate differences. Among these residues, Thr59 of nAChR β2 may interfere with effective access to the binding site whereas Lys59 may facilitate this binding.